Co‐designing the environmental land management scheme in England: The why, who and how of engaging 'harder to reach' stakeholders. Issue 3 (29th March 2022) - Hurley, Paul; Lyon, Jessica; Hall, Jilly; Little, Ruth; Tsouvalis, Judith; White, Veronica; Rose, David Christian
Abstract: Agriculture around the world needs to become more environmentally sustainable to limit further environmental degradation and impacts of climate change. Many governments try to achieve this through enrolling farmers in agri‐environment schemes (AES) that encourage them to undertake conservation activities. Studies show that AES can suffer from low uptake, meaning their environmental objectives remain unattained. To succeed for people and nature, policy‐makers are increasingly adopting multi‐actor approaches in the 'co‐design' of AES to make them more attractive and inclusive of a full range of stakeholders, including 'harder to reach' farmers. To address why some land managers (principally farmers) may be harder to reach in the context of co‐designing England's new Environmental Land Management (ELM) approach, we undertook a quick scoping review of the literature, conducted 23 first‐round and 24 s‐round interviews with key informants, and held a workshop with 11 practitioners. We outline why farming stakeholders may be harder to reach and how policy‐makers can adjust the engagement process to make co‐design more inclusive. Based on the results, we make recommendations that could help policy‐makers to design better, more inclusive AES that would attract greater uptake and increase their chances of success. Read the free Plain Language Summary for this article on the Journal blog. Abstract : Read the free Plain Language Summary for this article on the Journal blog.